Efeito do Quorum Sensing na Motilidade e na Multiplicação de Salmonella Typhimurium. - Conceição, Rita de Cássia dos Santos da (2012)
Salmonella spp. is the most commonly bacterium transmitted through contamined food. The foods of animal are the most responsible for the worldwide distribution of this bacterium. Salmonella spp. is able to induce a variety of diseases, ranging from an enteric fever, septicemia, gastroenteritis and infections focused. This is due to the bacteria produce different pathogenicity factors and these factors, the flagellum was the target of our study and it is one of the pathogenicity factors induced by Quorum Sensing. Quorum Sensing is a bacterial signaling system that operates through the so-called autoinducer (AI). Gram-negative bacteria produce three auto-inducers. Studies find that catecholamines are able to use the same pathway the autoinducer 3 (AI-3) to active certain genes. Epinephrine and norepinephrine are catecholamines that are present in the mammalian gastrointestinal tract can modulate bacterial gene expression. This work had as objectives to evaluate the Quorum Sensing signaling system on motility, on the growth and flagellar assembly gene expression of Salmonella enterica serovar Typhimurium (ST) and do a review about pathogenicity factors of Salmonella spp. induced by Quorum Sensing. ST was exposed to different concentrations of epinephrine and conditioned medium and its association. The combination of 500 μM epinephrine with 50 % conditioned medium increased ST bacterial motility, growth and increased the expression of the fliC, motA, motB and fliA genes. These results suggest that epinephrine in association with conditioned medium increases ST growth and motility, by modulating the expression of genes involved in flagellum assembly. These observations provide valuable insight into the association between catecholamine and autoinducer and their role in the outcome of Salmonella spp. infection.